(untitled) (Educational Knowledge, 2024)
This research, stemming from an exhaustive documentary review, endeavors to systematically integrate theoretical, epistemic, and practical perspectives concerning the culture of peace, citizenship education, and human rights. These multidimensional facets are posited as the foundational axis, strategically embedded within curricular frameworks to facilitate the nuanced construction of democratic and pluralistic societal structures. The focal point of this study revolves around the methodical promotion of universal values, accentuating the cultivation of attitudinal and behavioral resources that serve to fortify the underpinnings of communal existence. The ultimate objective is the meticulous restoration of the intricate social fabric, engendering reconciliation, and establishing environments wherein the common good, equitable treatment among members, and functional efficacy synergistically contribute to an elevated quality of life. In summation, the notion of dignified coexistence becomes intricately entwined with the pedagogical endeavor to impart meaningful lessons in universal human values. This approach is underpinned by a profound acknowledgment of principles such as self-determination, personal autonomy, and impartial treatment among individuals. The overarching aspiration of this academic pursuit lies in the comprehensive education of citizens, equipped to make positive and enduring contributions to the construction of societies grounded in principles of peace, democracy, and inclusion